Sarkofagus Samosir: Kreativitas Lokal Masyarakat Samosir - Taufiqurrahman Setiawan (Balai Arkeologi Sumatera Utara, 2009)
AbstractOne of the megalithic culture is sarcophagus. It appeared in someplace in Indonesia, such as Sulawesi, Nusa Tenggara, Bali, and also Sumatera. All has same function, as a sarcophagus, yet each has spescial characteristic.